MEAN DIFFERENCE OF ZINC AND SELENIUM LEVELS AND TUBERCULOSIS OUTCOMES IN CHILDREN RECEIVING TREATMENT IN INDONESIA - Masrul, Masrul; USMAN, Elly; YANI , Finny Fitry (African Journal of Infectious Diseases (AJID), 2025)
Background: Tuberculosis (TB) remains a significant health issue, particularly among children in TB-endemic regions. Micronutrient deficiencies, such as zinc and selenium, may influence TB treatment outcomes. However, the relationship between these micronutrients and TB outcomes in children is not well-established in Indonesia. This study aimed to investigate the mean difference of zinc and selenium levels on TB treatment outcomes in children receiving treatment in Padang, Indonesia. Materials and Methods: A cross-sectional study was conducted at the district level hospitals in Padang City, Indonesia, from April to October 2024. The study included children aged 1–14 years diagnosed with TB and receiving treatment. Serum zinc and selenium levels were measured using Chemiluminescent Immunoassay (ECLIA). The treatment outcomes were categorized as success (cured and completed treatment) or failure (death, treatment failure, or default). Results: Zinc levels were significantly lower in the failure group (71.61±8.18 ng/mL) compared to the success group (79.72±8.12 ng/mL) (P<0.05). Similarly, selenium levels were lower in the failure group (89.56±23.47 ng/mL) compared to the success group (115.09±17.86 ng/mL) (P<0.05). Conclusion: The study found a significant association between lower zinc and selenium levels and unsuccessful TB treatment outcomes in children. These findings suggest that addressing micronutrient deficiencies may play an important role in improving TB treatment outcomes in pediatric populations. Further research is needed to explore potential interventions to improve micronutrient status in TB patients.